Soil health as a proxy for long-term reclamation success of metal-contaminated mine tailings using lime and biosolids - James A. Ippolito; Liping Li; Travis Banet; Joe E. Brummer; Cassidy Buchanan; Aaron R. Betts; Kirk Scheckel; Nick Basta; Sally L. Brown (Elsevier, 2024)
Mine lands contaminted with heavy metals pose environmental risks, and thus reclamation is paramount for improving soil, plant, animal, and ecosystem health. A metal-contaminated alluvial mine tailing, devoid of vegetation, received 224 ​Mg ​ha−1 of both lime and biosolids in 1998, and long-term reclamation success was quantified in 2019 with respect to soils, plants, and linkages to animals. Reclamation success was quantified using the Soil Management Assessment Framework (SMAF), in conjunction with bioavailable (0.01 ​M CaCl2 extractable) and plant-available (Mehlich-3 extractable) soil metal concentrations, X-ray absorption spectroscopy, plant metal concentrations, and plant quality characteristics. Results showed that all soil indicators were improved in successfully-reclaimed areas as compared to on-site degraded areas, including increases in soil aggregate stability, pH, plant-available P and K, soil organic C, potentially-mineralizable N, microbial biomass C and β-glucosidase activity and decreases in soil bulk density and electrical conductivity. Of indicators, unitless soil health scores were assigned based on the SMAF, with data suggesting that bulk density, wet aggregate stability, potentially- mineralizable N, microbial biomass C, pH, and electrical conductivity should be monitored in the future. The long-term effects of lime and biosolids application have improved soil physical, biological, and overall soil health. Plant metal concentrations have decreased by an order of magnitude since early reclamation, with most plant metal concentrations being tolerable for domestic livestock consumption. From an animal health perspective, feeding grasses from this site during latter parts of a growing season may need supplemental feed to provide greater protein and energy content, and to reduce potentially-harmful Cd concentrations from food chain bioaccumulation. However, a health concern exists based on soil bioavailable Cd and Zn concentrations that exceed ecological soil screening levels. Still, plants have stabilized the soil and acidity remains neutralized, leading to long-term improvements in soil health, with overall improved ecosystem health.